PROFESSIONAL DEVELOPMENT OF A PEDAGOGUE AND ICT-COMPETENCY FOR TEACHERS - Alexander V. Khoroshilov (Высшее образование в России)
The article describes UNESCO IITE experience on creation of new pedagogical qualification characteristics of the teacher development during the transition period to digitalpedagogics in the open global educational environment. The UNESCO document «ICT Competency Framework for Teachers. UNESCO recommendations» published in many languages became a basis for development of national (regional) standards on ICT competence of teachers and development of clear national (regional) policy in this area.